2016
DOI: 10.1038/srep34919
|View full text |Cite
|
Sign up to set email alerts
|

A novel Al matrix composite reinforced by nano-AlNp network

Abstract: In pursuit of lightweighting of automobiles and low emission of transportation, the efforts to develop high-strength, heat-resistant and fatigue-resistant Al alloys and/or composites have been ongoing. Here we report a novel Al matrix composite with ultrahigh strength reinforced by a three dimensional network of nano-AlN particles for the first time. The in-situ synthesized AlN particles are connected by twinning bonding chains and built up a three dimensional network strengthening Al matrix enormously like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 36 publications
(40 reference statements)
2
27
0
2
Order By: Relevance
“…Ma et al . 12 reported a novel Al matrix composite with ultrahigh strength reinforced by a three dimensional network of nano-AlN particles. Hossein 13 found that the ferrite was grain-refined to about 3 μm due to vitue of augmented nucleation and retarded growth by titanium oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al . 12 reported a novel Al matrix composite with ultrahigh strength reinforced by a three dimensional network of nano-AlN particles. Hossein 13 found that the ferrite was grain-refined to about 3 μm due to vitue of augmented nucleation and retarded growth by titanium oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Palanikumar et al (2019) combined B 4 C (primary reinforcement) and Mica (secondary reinforcement) particles and reported an increase in wear strength of the hybrid when compared with the composite produced by only the primary reinforcement. The use of titanium diboride for grain refinement (Xi et al, 2020) as well as carbides, nitrides, compounds of oxides, organic, inorganic, and industrial waste sourced form of reinforcement particles at micrometres and nanometres sizes for remarkable improvement in properties of AMCs have also been documented (Chen et al, 2020;Ma et al, 2016;Tiku et al, 2020). Several other studies have also reported the use of hybrid and other forms of reinforcement particles in the synthesis of AMCs (Arora & Sharma, 2018;Gowrishankar et al, 2019;Krushna et al,…”
Section: Hybrid and Other Reinforcement Materialsmentioning
confidence: 99%
“…Recently, AlN/Al nanocomposites reinforced with inhomogeneous distributed AlN network have been prepared by liquid-solid in situ reaction in our previous work [ 12 ]. It is revealed that the network-rich region can be effectively strengthened by AlN network, and the network-lean region supplies the ductility of composites due to the coarse matrix grains.…”
Section: Introductionmentioning
confidence: 99%